Analysis of Determinant Factors Influencing Compliance with Patient Safety Incident Reporting Based on the Theory of Planned Behaviour - Alfi Yudisianto; Nurwijayanti; Prima Dewi Kusumawati (Health and Technology Journal (HTechJ), 2025)
Patient safety is a priority for healthcare services because it can lead to serious public health issues. Incident reporting is crucial for enhancing patient safety. This study aims to analyze the determinants of patient safety incident reporting compliance using the Theory of Planned Behavior. This study employed a cross-sectional design, with the population consisting of medical and nursing staff, involving 116 participants selected using a simple random sampling technique. The analysis in this study used Logistic regression analysis. The study found that health professionals reported high levels of bullying (56.9%), poor patient safety culture (75.0%), low protection motivation (53.4%), and non-compliance in reporting patient safety incidents (55.2%). Logistic regression analysis, which had the potential to comply with incident reporting, showed low bullying (aOR: 1.8; 95% CI: 0.69-4.81), good patient safety culture (aOR: 2.9; 95% CI: 0.93-9.25), and high protection motivation (aOR: 1.91; 95% CI: 0.86-4.25). The importance of analyzing the factors that influence compliance in reporting patient safety incidents is based on the theory of planned behavior, which suggests that low workplace bullying, a good patient safety culture, and high protection motivation are the primary determinants of compliance in reporting patient safety incidents.